2005
DOI: 10.1080/02841850510021382
|View full text |Cite
|
Sign up to set email alerts
|

Islets of meningioma in an acoustic schwannoma in a patient with neurofibromatosis-2: pathology and magnetic resonance imaging findings

Abstract: Mixed tumors of the cerebellopontine angle, composed of meningioma and schwannoma components, are extremely rare; so far, only 12 cases have been reported in the literature. They are thought to be exclusively associated with neurofibromatosis-2. We present a mixed tumor of schwannoma and meningioma in a patient with neurofibromatosis-2 and discuss the pathology and magnetic resonance imaging (MRI) findings in relation to the literature. Review of the literature shows that a typical MRI pattern has not been est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The metaplasia hypothesis proposes metaplasia of cell lines with meningoepithelial cell pockets, which later proliferate, giving rise to tumors. 5 The stimulus hypothesis suggests that schwannoma may act as a stimulus, causing a meningothelial reaction and giving rise to meningioma. Pallini et al 6 reported a synergistic effect of one tumor over the development and growth of another through an autocrine or paracrine growth-stimulatory mechanism that involved an epidermal growth factor (EGF)-like factor.…”
Section: Discussionmentioning
confidence: 99%
“…The metaplasia hypothesis proposes metaplasia of cell lines with meningoepithelial cell pockets, which later proliferate, giving rise to tumors. 5 The stimulus hypothesis suggests that schwannoma may act as a stimulus, causing a meningothelial reaction and giving rise to meningioma. Pallini et al 6 reported a synergistic effect of one tumor over the development and growth of another through an autocrine or paracrine growth-stimulatory mechanism that involved an epidermal growth factor (EGF)-like factor.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Since their occurrence was first described by Cushing and Eisenhart 15 in 1938, just over a dozen case reports of mixed schwannomas and meningiomas (both components seen together in the same tumor) arising in patients with NF-2 have been published. [1][2][3][4] Even more rarely, with just 3 case reports to our knowledge, mixed schwannomas and meningiomas have been reported in patients without definite clinical evidence of NF-2. [6][7][8] In all 3 cases, the mixed tumor was located in the cerebellopontine angle.…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few single case reports in the literature. [1][2][3][4] However, Geddes et al 5 reported a series of 5 such tumors in 4 patients. There are even rarer case reports of such mixed tumors in patients without definite evidence of NF-2.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first description by Cushing and Eisenhart in 1938, just over a dozen case reports of mixed schwannomas and meningiomas (both components seen together in the same tumor) arising in patients with NF2 were reported [1]. The simultaneous occurrence of primary brain tumours of different histology in the same anatomical site its´ a rarely observed situation, more rarer particularly on the CPA [2,3].…”
Section: Introductionmentioning
confidence: 99%